Emergency responder injuries and fatalities : an analysis of surveillance data - Houser, Ari.; Jackson, Brian A. (Brian Anthony); Bartis, James T., 1945-; Peterson, D. J.; Science and Technology Policy Institute (Rand Corporation); Rand Corporation; National Personal Protective Technology Laboratory; National Institute for Occupational Safety and Health (Santa Monica, CA : RAND, 2004)
The mission of the National Personal Protective Technology Laboratory (NPPTL) is to reduce and prevent occupational disease, injury, and death of workers by advancing federal research on personal protective technologies. NPPTL asked RAND to review available databases that provide disease, injury, and fatality data pertinent to emergency response functions and the role of personal protective technology. This report collects and synthesizes available data on casualties experienced by the emergency responder population for the purpose of estimating the frequency, causes, and characterization of those casualties. The authors examined data separately for firefighters, police officers, and emergency medical technicians (EMTs). They also broke down the data by nature of injury, incidence of injury, activity in which the responder was engaged when injured, and seriousness of injury. The greatest amount of data exist for the firefighter community; a lesser amount for police officers. Data for EMTs are still scarce, but this situation is improving. The available data can provide a route for identifying combinations of kinds and causes of injury, body parts involved, and types of responder activity where injury reduction efforts might be most effectively applied.
Introduction -- The Emergency Responder Population -- Available Surveillance Data Sources to Define the Occupational Injury and Disease Characteristics of the Emergency Responder Workforce -- Observations from the Data Regarding Risks Faced by Emergency Responders -- Conclusions -- App. A: RAND Injury and Fatality Classification System -- App. B: Fatality, Injury, Illness, and Exposure Numerical Data Tables.
"March 2004."
"RAND Science and Technology."
Includes bibliographical references (p. 57-60).
Also available on the internet via WWW in PDF format.
Keywords: Emergency management -- United States; Emergency medical personnel -- Health and hygiene; Emergency medical personnel -- Wounds and injuries; Emergency medical personnel -- United States -- Safety measures